Sistem Informasi Manajemen (SIM) dalam Pengelolaan Pendidikan di Lingkungan Sekolah Dasar - Rahmawati, Dila; Nurcahya, Intan; Aliyah, Rusi Rusmiati (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze strategies for using Management Information Systems (MIS) in educational management in elementary schools. The study used a qualitative descriptive method through a literature review of various academic sources obtained through Google Scholar. The research focused on the implementation of MIS, key success strategies, benefits and barriers to implementation, and stakeholder engagement. The study results indicate that MIS implementation in elementary schools plays a significant role in improving administrative efficiency, accelerating data-driven decision-making processes, and strengthening transparency and accountability in school management. Key strategies for success include establishing a vision and mission that supports digitalization, strengthening infrastructure and human resource training, utilizing data for analysis and recommendations, active stakeholder involvement (teachers, parents, and committees), and regular monitoring and evaluation. However, MIS implementation still faces various challenges, such as limited infrastructure, low digital literacy, suboptimal data quality, and resistance to changes in manual work culture. To overcome these obstacles, schools need to build an adaptive digital culture, conduct ongoing training, and strengthen school leadership in digital transformation. Overall, effective strategies for MIS use in elementary schools can promote more efficient, accountable educational governance, and be oriented towards improving the quality of learning.